COLLABORATIVE GOVERNANCE PLUS MULTI-HELIX MODEL FOR POVERTY ALLEVIATION IN THE ROKAN BLOCK: LESSONS FROM THE INDONESIAN OIL AND GAS INDUSTRY - Falah Amru, Nasyirul (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2025)
As Indonesia's top producer of oil and gas, the Rokan Piece in Riau Territory contributes significantly to the country's GDP. However, the area continues to descend into extreme poverty despite its wealth, exemplifying the asset revile catch-22. The deployment of the Collaborative Administration Additionally Multi-Helix (CGPMH) system is examined in this study as a crucial strategy to overcome these socioeconomic disparities. The CGPMH demonstrates how to coordinate the joint efforts of the government, business community, academic community, civil society, and media in order to establish cooperative agreements for the reduction of poverty in areas with abundant resources. This study used a subjective case study approach to gather data from field observations, record audits, and in-depth interviews carried out in the Siak and Bengkalis Regencies. The findings reveal that current government agreements, particularly those pertaining to revenue-sharing elements, have been ineffective because they lack the ability to regulate locally and provide skewed benefit transfer. In the meanwhile, more significant arrangements are needed to increase the profitability of corporate initiatives like Corporate Social Responsibility (CSR) programs and capacity-building projects led by academics.